Implementasi Penyaluran Kredit Usaha Rakyat (KUR) Super Mikro dalam Meningkatkan Kesejahteraan Masyarakat - Mustafa Mustafa; Hajar Hajar; Bakri Bakri (Al-Buhuts, 2022)
The purpose of this study was to find out how far the distribution of super micro people's business credit funds is in improving people's welfare. This research was conducted using a qualitative method with a phenomenological approach, the data collection technique was carried out by interviewing related parties, namely the head of the BRI unit in the province of Gorontalo. The results of the study revealed that the implementation of the People's Business Credit Program at BRI units in the community has been going well where the down payment is <10,000,000 with a loan fee of 6%, by visiting from door to door directly, can strengthen the community's economy in developing their business.